1995
DOI: 10.1515/jpme.1995.23.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Motor responsivity during habituation testing of normal human fetuses

Abstract: Features of fetal motor responsivity include both the magnitude of the startle response elicited by a single stimulus (i.e., basal reactivity) and the ease by which responding to successive stimuli is inhibited (i.e., habituation). We examined basal motor reactivity and habituation of the motor response in 56 normal human fetuses between 34 and 40 weeks of gestation. Testing consisted of 8 trials of a 1-sec vibroacoustic stimulus (VAS) with a 10-sec interstimulus interval. A score of 0-10 was assigned for each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Thus, there are both in vitro and in vivo findings indicating that the placenta detects and responds to a variety of maternal physiological and psychological stress signals supporting the conclusion that levels of pCRH reflect fetal exposure to maternal stress. This conclusion is supported by findings from several studies that reported an impact of prenatal maternal psychosocial state on human fetal behavior [Van den Bergh et al, 1989; Groome et al, 1995; Sjostrom et al, 1997; Monk et al, 2000; DiPietro et al, 2002; Monk et al, 2003]. …”
Section: Discussionsupporting
confidence: 74%
“…Thus, there are both in vitro and in vivo findings indicating that the placenta detects and responds to a variety of maternal physiological and psychological stress signals supporting the conclusion that levels of pCRH reflect fetal exposure to maternal stress. This conclusion is supported by findings from several studies that reported an impact of prenatal maternal psychosocial state on human fetal behavior [Van den Bergh et al, 1989; Groome et al, 1995; Sjostrom et al, 1997; Monk et al, 2000; DiPietro et al, 2002; Monk et al, 2003]. …”
Section: Discussionsupporting
confidence: 74%
“…Fetal reaction usually entails a startle response consisting of increased movement and heart rate that then declines over trials (Groome, Singh, Burgard, Neely, & Deason, 1995;Groome, Watson, & Dykman, 1994). Fetal response to vibratory stimulation begins at about the 26th week of gestation and reaches maturity at about 32 weeks (Kisilevsky, Muir, & Low, 1992).…”
Section: Fetal Actocardiographic Monitoring and Vibratory Stimulationmentioning
confidence: 99%
“…63 In contrast to studies which have presented stimuli until the fetus ceases responding, 31 ' 34 others have not habituated the fetus until the cessation of the response but have presented a fixed number of stimuli (e.g. 3, M 8, 37 14, 35 20, 43 40, 47 ) and noted the fetus's response to this. This is an inherent problem in the latter type of study in that individuals may not be equally habituated when the final stimulus of the sequence has been presented.…”
Section: Response Characteristicsmentioning
confidence: 99%